موسمیاتی تغیرات اور ہماری اجتماعی ذمہ داری ؛ ابلاغی و سیاسی نقطہء نگاہ سے سیر ت طیبہ ﷺ کی روشنی میں ایک جائزہ: Climate Change and Our Responsibilities; A review from the communication and political point of view in the light of the Sirah of the Holy Prophetﷺ - Begum , Dr. Abida; Amjad , Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
Climate change is a global crisis that demands urgent attention and collective duty. Keeping the environment clean is an important part of the Prophet’s teachings. According to Islamic teachings, cleanliness is half faith. Being a Muslim what is our collective responsibility to cope with the climate change and what should be the role of the government and especially the media in this regard. How can we protect the society and the environment ethically? The Holy Prophet ﷺ was sent with perfect religion not only as a Mercy for humans but for the whole world. And, apart from jinn and human beings, universe and its atmosphere are also entitled to Prophet’s Mercy; who are the beneficeries of that natural world with its climate. The essence of this paper is to create awareness about our collective responsibilities regarding the protection of ecosystem in the light of teachings of the Noble Prophet ﷺ. Key Words: Environment, Pollution, Media, Responsibilities, Sirat -un-Nabiﷺ